Tetraethylammonium L-tartarate dihydrate - Abdul Rahman, Mohd Basyaruddin; Jumbri, Khairulazhar; Sirat, Kamaliah; Kia, Reza; Fun, Hoong Kun (International Union of Crystallography, 2008)
In the crystal structure of the title compound, C8H20N+·C4H5O6−·2H2O, the ions and water molecules are linked via O—H...O and C—H...O hydrogen bonds, forming a two-dimensional network parallel to (001).